Human impact on low-land Vellayani Lake, south India: A record since 3000 yrs BP - M.P. Veena; Hema Achyuthan; Chris Eastoe and Anjum Farooqui (Anthropocene, 2014)
Humans have continuously changed the landscape and vegetation cover of the earth, including deserts and lake margins. Vellayani Lake, Kerala, is being severely affected by human activity in the catchment basin. Population increase, leading to increased demand for agricultural land and water, is driving a positive feedback loop resulting in the accelerating siltation of the lake and lowering of water levels. A 145 cm sediment core represents deposition since 3000 yrs BP, but at least half of the sediment has been deposited since 1650 AD, possibly since 1950 AD. The sediment stratigraphy is disturbed, most likely by slumping since 1970, of an unstable sediment accumulation near the lake margin. The disturbance precludes detailed interpretation of paleoenvironmental proxies, textural variation, chemical weathering index, pollen and phytolith assemblages. The proxies provide evidence of drier climate up to 3000 yrs BP, and wetter conditions at about 1210 yrs BP. Low frequency of phytoliths morph types indicates reduction in vegetation cover and a significant increase in grassland since 2300 yrs BP due to climate warming, weakened southwest monsoon, deforestation reclamation of the lake margins for intensive agricultural practices. Occurrence of diatoms and sponge spicules indicate shallowing of the lake from 2300 yrs BP onwards. Occurrence of charcoal pieces post 3000 yrs BP represents human impact. Integration of all the results show that the Vellayani Lake has contracted because of a weakened Indian southwest monsoon since 3000 yrs BP, intense human impact in the form of deforestation, irrigation and agricultural practices.